BMP use in the surgical treatment of pyogenic spondylodiscitis: Is it safe?. (January 2022) - Yaw Tee, Lawrence Yoon; Hunter, Sarah; Baker, Joseph F.
Highlights: Use of BMP in the setting of pyogenic spondylodiscitis is controversial. Patients who have undergone surgery with and without BMP were compared. BMP utilisation group shows no greater infection recurrence. BMP- related complications is uncommon. Osteoinductive properties of BMP is preserved even in the setting of infection. Abstract: Objective: Use of BMP in the setting of infection remains controversial. We examined the safety and effectiveness of BMP in the surgical treatment of pyogenic spondylodiscitis and compared patients who have been treated with or without BMP during surgery. Methods: 57 patients who have undergone surgery for pyogenic spondylodiscitis after presenting to a tertiary Spine referral institution between 2011 and 2020 were included. 18 underwent surgery alone without BMP and 39 underwent surgery with BMP. Outcomes were compared between the two groups, including re-operations, infection recurrences, BMP- related complications and radiological fusion. Results: The cohort comprised 41 males (71.9%) with a mean age 63.7 +/- 13.3 years. Surgical indications include instability (n = 18), pain (n = 4), neurological deficit (n = 15) and sepsis or failure of non-operative management (n = 20). In the group who underwent surgery without BMP, there were two cases of re-operation for infection recurrence (11.1%) and three cases of cage subsidence; 80% achieved definitive and probable fusion. In the group who underwent surgery with BMP, there were three cases of re-operation for infection recurrence (7.7%), three cases of cage subsidence and one case of BMP- related radiculitis; 96.5% achieved definitive and probable fusion. Conclusions: The use of BMP in the surgical treatment of pyogenic spondylodiscitis did not confer an increased risk of infection recurrence, revision surgery or radiculitis. BMP can be a useful and safe adjunct in surgical intervention for pyogenic spondylodiscitis.